REEVALUATING MEAN ARTERIAL PRESSURE TARGETS IN SEPSIS AND SEPTIC SHOCK: INSIGHTS FROM A SYSTEMATIC REVIEW AND META-ANALYSISREEVALUATING MEAN ARTERIAL PRESSURE TARGETS IN SEPSIS AND SEPTIC SHOCK: INSIGHTS FROM A SYSTEMATIC REVIEW AND META-ANALYSIS - MADHU A YADAV; REKHA A ASSADI; G H MIDHUN KUMAR; NEHA K KUDUMULA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
The conflicting evidence on the clinical impact of higher versus lower mean arterial pressure (MAP) targets in sepsis and septic shock underscores the urgent need to redefine optimal MAP thresholds to improve outcomes in these critical illnesses. This systematic review and meta-analysis adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines. A data search was conducted on July 1, 2024, for randomized controlled trials and observational studies published from January 2004 to December 2023, assessing patient outcomes based on MAP goal parameters. The primary outcomes were all-cause mortality and overall adverse events. Patients with elevated MAP targets exhibited significantly higher odds of all-cause mortality (odds ratio [OR]: 1.10, 95% confidence interval [CI]: 1.00–1.22), atrial fibrillation (OR: 2.52, 95% CI: 1.25–5.07), and supraventricular arrhythmia (OR: 1.81, 95% CI: 1.07–3.04) compared to those with lower MAP targets (all p≤0.05). In contrast, higher MAP patients with chronic hypertension and sepsis had significantly lower odds of requiring renal replacement therapy (RRT) (OR: 0.77, 95% CI: 0.62–0.97; p=0.03). No significant differences were observed in overall adverse events, acute myocardial infarction, intensive care unit length of stay, major bleeding, mesenteric ischemia, RRT, 28-day survival, or ventricular tachycardia between the groups. This study highlights that targeting higher MAP in sepsis patients may elevate the risk of cardiac complications, such as atrial fibrillation and supraventricular arrhythmia, without having substantial benefits in reducing mortality or adverse events. The conflicting evidence on the clinical impact of higher versus lower mean arterial pressure (MAP) targets in sepsis and septic shock underscores the urgent need to redefine optimal MAP thresholds to improve outcomes in these critical illnesses. This systematic review and meta-analysis adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines. A data search was conducted on July 1, 2024, for randomized controlled trials and observational studies published from January 2004 to December 2023, assessing patient outcomes based on MAP goal parameters. The primary outcomes were all-cause mortality and overall adverse events. Patients with elevated MAP targets exhibited significantly higher odds of all-cause mortality (odds ratio [OR]: 1.10, 95% confidence interval [CI]: 1.00–1.22), atrial fibrillation (OR: 2.52, 95% CI: 1.25–5.07), and supraventricular arrhythmia (OR: 1.81, 95% CI: 1.07–3.04) compared to those with lower MAP targets (all p≤0.05). In contrast, higher MAP patients with chronic hypertension and sepsis had significantly lower odds of requiring renal replacement therapy (RRT) (OR: 0.77, 95% CI: 0.62–0.97; p=0.03). No significant differences were observed in overall adverse events, acute myocardial infarction, intensive care unit length of stay, major bleeding, mesenteric ischemia, RRT, 28-day survival, or ventricular tachycardia between the groups. This study highlights that targeting higher MAP in sepsis patients may elevate the risk of cardiac complications, such as atrial fibrillation and supraventricular arrhythmia, without having substantial benefits in reducing mortality or adverse events.